2009
DOI: 10.2147/ndt.s4184
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment after cerebrovascular stroke: Relationship to vascular risk factors

Abstract: Background: Cognitive decline after cerebrovascular stroke has adverse outcome consequences. Since some vascular causes can be prevented and treated, the identifi cation of stroke-related cognitive impairment is a challenge. Patients with cognitive impairment and vascular diseases exhibit higher homocysteine (Hcy) concentrations. Whether Hcy is an independent risk factor for cognitive impairment after stoke is still in question. The objectives of this study were to determine: 1) the relative frequency of fi rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 84 publications
0
14
0
1
Order By: Relevance
“…The frequency of dementia after cerebrovascular stroke (CVS) varies between studies, ranging between 21 and 37% [35,36]. In the present study only 15.6% of cases had dementia.…”
Section: Discussionmentioning
confidence: 47%
“…The frequency of dementia after cerebrovascular stroke (CVS) varies between studies, ranging between 21 and 37% [35,36]. In the present study only 15.6% of cases had dementia.…”
Section: Discussionmentioning
confidence: 47%
“…Additionally, the type of cognitive impairment observed post-stroke varies; often including deficits in measures of global cognition, as well as domain-specific impairments involving executive function, language, visuospatial ability, and memory[ 56 ]. Some previously identified risk factors for the development of PSCI, including family history of dementia and individual cardiovascular risk factors[ 8 ], could not be controlled for given the sample size. Although all efforts were made to control for potentially confounding variables, pre-stroke cognitive capacity and white matter disease burden were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of post-stroke MMSE scores less than 24, indicative of significant cognitive impairment, was much higher than the prevalence of dementia diagnosed by standard criteria, which included the DSM-IV or ICD-10[ 7 ]. The majority of these and other known risk factors for PSCI including older age, lower level of education, family history of dementia [ 8 ] are not readily amenable to treatment. Therefore, there is considerable need to identify pathophysiological mechanisms that may contribute to PSCI.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Khedr et al, 14 AF was more common among patients with PSD, although no significant association with PSD could be established. On the other hand, in 2000, Barba et al 1 found correlations between cognitive decline and AF.…”
Section: Discussionmentioning
confidence: 90%